"Neither here nor there" - Flattening, omission, and silencing, in the constructing of identity of Islamic girls who attend a Jewish school. Issue 1 (2nd January 2020) - Ben-Asher, Smadar; Ben-Yehoshua, Naama Sabar; Elbedour, Aya
ABSTRACT: The article presents narratives of young Bedouin women who attended Jewish schools. An analysis of in-depth interviews conducted with eight young women after they graduated high school and completed academic graduate studies was carried out by examining three mechanisms of choice of identity (Spector-Mersel) through the prism of the unsayable. The findings show a process fraught with representations of personal and social identities, demonstrating differences between their traditional society and the Western society in which they were educated. These point to the strength, security, and autonomy that these students developed, while also reflecting the high cost they had to pay.